2020
DOI: 10.1002/hbm.25139
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo mesoscopic diffusion MRI correlates with seizure frequency in patients with uncontrolled mesial temporal lobe epilepsy

Abstract: The role of hippocampal connectivity in mesial temporal lobe epilepsy (mTLE) remains poorly understood. The use of ex vivo hippocampal samples excised from patients with mTLE affords mesoscale diffusion magnetic resonance imaging (MRI) to identify individual cell layers, such as the pyramidal (PCL) and granule cell layers (GCL), which are thought to be impacted by seizure activity. Diffusion tensor imaging (DTI) of control (n = 3) and mTLE (n = 7) hippocampi on an 11.7 T MRI scanner allowed us to reveal intra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 70 publications
(117 reference statements)
1
20
0
Order By: Relevance
“…The precise correlation between WM integrity and seizure frequency remains unclear in BECTS. Interestingly, many other epilepsy syndromes, such as temporal lobe epilepsy and juvenile myoclonic epilepsy, have demonstrated that greater WM abnormalities are associated with the higher frequency of seizures [53,54]. These findings and ours raise the possibility that repetitive seizures could promote progressive WM impairment across epilepsy syndromes.…”
Section: Discussionsupporting
confidence: 66%
“…The precise correlation between WM integrity and seizure frequency remains unclear in BECTS. Interestingly, many other epilepsy syndromes, such as temporal lobe epilepsy and juvenile myoclonic epilepsy, have demonstrated that greater WM abnormalities are associated with the higher frequency of seizures [53,54]. These findings and ours raise the possibility that repetitive seizures could promote progressive WM impairment across epilepsy syndromes.…”
Section: Discussionsupporting
confidence: 66%
“…Previous ex vivo studies in hippocampus mostly focused on the hippocampal body or middle hippocampus (Ke et al, 2020 ; Ly et al, 2020 ), which has a dark band with a “C” or reversed “C” shape in T2‐weighted image as a hallmark for segmenting the subfields and layers (de Flores et al, 2020 ). The anterior part of hippocampus is more complex with more folds and larger individual variances than the middle part (de Flores et al, 2020 ; DeKraker et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent ex vivo study in hippocampal body using DTI found that patients with mesial temporal lobe epilepsy exhibited a larger variance in dMRI measures in hippocampal layers compared to controls (Ke et al, 2020 ). Authors explained that this difference might reflect the variability in clinical measures (i.e., seizure severity or frequency).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations